Pengembangan Bahan Ajar Sastra Berbasis Al Bayani Untuk Siswa Kelas XI SMA - Mira Salviani; Mulyanto Widodo; Siti Samhati (Universitas Lampung, 2018)
The aim of this research is to develop literary teaching materials based on the Al Bayani model and test their feasibility in learning short stories in high senior schools. This research uses development through the Borg and Gall model. The procedures in this research are (1) preliminary research, (2) development of teaching materials, and (3) teaching materials or the products. The data sources in field trials were carried out in three schools, SMAS Tamansiswa, SMAN 17 and SMAN 9 Bandarlampung. Data analysis techniques are carried out by transferring quantitative and qualitative data. Quantitative data was qualitative data to obtain a data description and conclusions. The results of this research can converted in to